2015
DOI: 10.1111/jace.13561
|View full text |Cite
|
Sign up to set email alerts
|

Growth and Microstructure‐Dependent Hardness of Directionally Solidified WC–W2C Eutectoid Ceramics

Abstract: Directionally solidified WC-W 2 C ceramics containing 40 at% carbon, corresponding to the WC-W 2 C eutectoid composition, were produced by laser surface melt processing. The resulting microstructures showed a lamellar-type eutectic/eutectoid microstructure with the WC minor phase embedded in the W 2 C matrix phase. The interlamellar spacing (k) in the eutectoid regions followed the relationship Vk 3.8 = constant, with the smallest spacing of 331 AE 36 nm achieved in the 3.24 mm/s processed sample. The indentat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 29 publications
0
17
1
Order By: Relevance
“…calculated hardness of WC is slightly higher than the previously reported experimental values [37][38][39][40][41][42], whereas the hardness of W 2 C-ε is lower than previous experimental results [16,17,19,39,43].…”
Section: Accepted Manuscriptcontrasting
confidence: 71%
See 2 more Smart Citations
“…calculated hardness of WC is slightly higher than the previously reported experimental values [37][38][39][40][41][42], whereas the hardness of W 2 C-ε is lower than previous experimental results [16,17,19,39,43].…”
Section: Accepted Manuscriptcontrasting
confidence: 71%
“…In particular, hardness measured by indentation methods strongly depends on the testing load and time [16]; thus, the hardness of a sample can vary. Dense WC sintered bodies are also difficult to obtain by general vacuum sintering, and several studies have reported that carbon-deficient phases, such as W 2 C, that are softer than WC are frequently detected in WC sintered bodies [13,16,17,44]. Therefore, the experimental hardnesses are lower than the calculated hardnesses.…”
Section: Accepted Manuscriptmentioning
confidence: 93%
See 1 more Smart Citation
“…However, rigorous consideration of interface anisotropy and kinetics of the pattern selection process during solidification can explain deviations from the simplistic volume fraction criterion and variations in morphology with growth rate. 68,69 Also included in Table I is a WC-W 2 C eutectoid ceramic composite that has been explored by Chen, et al 70 During directional solidification from the melt, the system undergoes both eutectic and eutectoid transformations and series of solid-state transformations through various W 2 C polytypes. 65 In the B 4 C-MoB 2 eutectic, the irregular, "Chinese script" microstructure may be attributed to anisotropic interfacial energy.…”
Section: Overview Of Eutectic Compositions and Microstructuresmentioning
confidence: 99%
“…9(a). 70 Moreover, the preferred crystal orientation in these WC-W 2 C eutectoids corresponded to close-packed carbon directions (WC: [ 12 10], W 2 C: [ 12 10]) in both phases aligned parallel to each other within the interface place. 9(b) and (c).…”
Section: Texture and Crystallographic Orientation Relationshipsmentioning
confidence: 99%